Use of Mixture Design for the Sensory Evaluation of Carrot and Orange Juice - Raza, Irum; Bibi, Naseem; Khan, Muhammad Ahsan; Anwar, Muhammad Zubair; Bukhari, Sumaira (Pakistan Journal of Nutrition, 2014)
The present study was intended to use mixture design for the quality evaluation of mixed fruit juice. Juice was prepared with carrot and orange. The sensory evaluation for taste, texture, aroma, color and overall acceptability of carrot and orange mixed juice was subjected to a panel of six judges from FSPDI and SSRI. The results based on sensory evaluation showed that the overall acceptance level for treatment four specifically the blend with 75% carrot and 25% orange was highest (7). Mixture regression technique was used to select the best or the highly acceptable blend of carrot and orange juice. The results of mixture regression analysis showed no variation in the opinions of judges as regards to taste, texture, color, aroma and overall acceptability of the blends of juices because the p-values for all of the interaction components were greater than 0.05.